Analisis Yuridis Perlindungan Anak dalam Eksploitasi oleh Orang Tua melalui Paksaan Mengemis menurut UU No. 35/2014 dan KUHP - Dhamar Djati Sasongko; Maria Benedicta Azalia Putri; Aditya Arif Pratama; Ananda Thalia Wahyu Salsabilla (Perspektif Administrasi Publik dan hukum, 2025)
The exploitation of children by parents through forced begging is a serious violation of children's rights protected by national law. This study aims to analyze legal protection for children based on Law Number 35 of 2014 concerning Child Protection and the Indonesian Penal Code (KUHP). The research method used is normative juridical with a statutory approach. The analysis shows that the state firmly prohibits the exploitation of children and imposes criminal sanctions on parents who force their children to beg. This protection includes both preventive and repressive measures. The Penal Code also strengthens child protection through provisions regarding criminal acts against minors. However, the implementation faces obstacles such as economic conditions, cultural factors, and lack of supervision. Strengthening legal enforcement and raising public awareness are necessary to ensure that child protection is effectively carried out. This study concludes that although legal instruments are available, concrete steps are still needed to eliminate child exploitation practices within the family environment.